Floriculture: A comparative insight of environmental business opportunities in Indonesia and India - Titisari, Andari (Jurnal Bisnis Kehutanan dan Lingkungan, 2025)
Background: Floriculture, a specialized field within horticulture, focuses on the cultivation of ornamental plants such as cut flowers, potted plants, and garden plants. This study examines and compares the floriculture industries of India and Indonesia by analyzing production practices, export patterns, economic contributions, and the role of government policies. Methods: This article employs a Systematic Literature Review (SLR) approach, focusing on recent publications (2021-2024) from Google Scholar to explore floriculture trends in India and Indonesia. The literature selection follows the PRISMA guidelines, combining studies on production, exports, economic impact, and government policies to provide a comprehensive view of the floriculture sectors in both countries. Findings: India has made substantial progress in floriculture, particularly in cut flower exports, driven by supportive national programs such as the National Horticulture Mission (NHM) and the Agricultural and Processed Food Products Export Development Authority (APEDA). These initiatives have supported infrastructure development, market access, and technology upgradation, enabling India to strengthen its position in the global floriculture market. Indonesia, despite its enormous potential due to its biodiversity and tropical climate, faces challenges such as limited infrastructure and insufficient production to meet global demand. Conclusion: The findings highlight that increasing technological innovation, improving supply chain infrastructure, and implementing supportive policies are critical to unlocking the full potential of floriculture in both countries. For Indonesia, prioritizing infrastructure and market development is essential, while India can benefit from further innovation and expanded market access. Novelty/Originality of this article: The study underscores the importance of a strategic approach to capitalizing on global demand for ornamental plants, ensuring long-term growth and sustainability.